2016
DOI: 10.1002/dc.23606
|View full text |Cite
|
Sign up to set email alerts
|

FNAC Aided Diagnosis and Categorization of Hepatoblastoma:

Abstract: Hepatoblastoma is the most common primary malignant hepatic tumour of infancy and early childhood. Histologically hepatoblastomas are categorized into pure epithelial and mixed epithelial-mesenchymal types and epithelial type is further subcategorized into pure fetal type, fetal and embryonal type, pure embryonal, and small cell types. This categorization has been shown to have prognostic and therapeutic implication. Fine needle aspiration cytology (FNAC) is useful in pre-operative diagnosis and categorization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…They also highlighted the importance of cell block preparation and its use in ancillary investigations. Bera et al also described three cases of HBs diagnosed and categorized on cytology which was subsequently confirmed on histological examination …”
Section: Discussionmentioning
confidence: 93%
“…They also highlighted the importance of cell block preparation and its use in ancillary investigations. Bera et al also described three cases of HBs diagnosed and categorized on cytology which was subsequently confirmed on histological examination …”
Section: Discussionmentioning
confidence: 93%
“…Different studies have shown prognostic significance of this categorisation on FNAC/CB with pure foetal type having the best outcome 17 . Immuno‐reactivity for beta‐catenin was seen in all cases of HB and foetal types showed extensive PAS positivity 18 . Beta‐catenin along with its diagnostic utility, has prognostic significance also in HB 18 …”
Section: Discussionmentioning
confidence: 98%
“…Immuno‐reactivity for beta‐catenin was seen in all cases of HB and foetal types showed extensive PAS positivity 18 . Beta‐catenin along with its diagnostic utility, has prognostic significance also in HB 18 …”
Section: Discussionmentioning
confidence: 98%
“…Cytology of hepatoblastoma is usually highly cellular, with clusters of liver-like cells with vacuolated cytoplasm in the fetal variety and angulated cytoplasm along with high N:C ratio in the embryonal variety. 6 The cells are usually arranged in small clusters and sometimes acini. The mixed type of hepatoblastoma can have osteoid or chondroid matrix with stromal tissue, mature or immature fibrous tissue and hyaline cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Uncommon variants of hepatoblastoma such as small cell undifferentiated hepatoblastoma also need to be distinguished from UES. 6 Small cell undifferentiated hepatoblastoma resembles other round cell tumours with the addition of prominent eosinophilic nucleolus. The tumour cells usually show loss of INI1.…”
Section: Discussionmentioning
confidence: 99%